March: Book Three Book three - Lewis, John, 1940-2020; Aydin, Andrew; Powell, Nate (Marietta, GA : Top Shelf Productions, 2015)
A graphic novel account of some pivotal moments in the Civil Rights Movement.
School Library Journal starred, August 2016
Booklist starred, August 2016
Horn Book Starred, September 2016
Pub Weekly, August 2016
Kirkus Starred, July 2016
Voice of Youth Advocates (V.O.Y.A.), October 2016
Keywords: Lewis, John, -- 1940-2020 -- Comic books, strips, etc; United States. -- Congress. -- House -- Comic books, strips, etc; Student Nonviolent Coordinating Committee (U.S.) -- Comic books, strips, etc; Civil rights movements -- Southern States -- History -- 20th century -- Comic books, strips, etc; African American legislators -- Comic books, strips, etc; African Americans -- Civil rights -- Comic books, strips, etc; Legislators -- United States -- Comic books, strips, etc; Civil rights workers -- United States -- Comic books, strips, etc; African American civil rights workers -- Comic books, strips, etc